WHERE LIBERALS AND CONSERVATIVES MEET: A NETWORK ANALYSUS OF POLITICAL NEWS SITE AUDIENCES - Nelson, Jacob; Webster, James (AoIR Selected Papers of Internet Research, 2015)
Political polarization is increasing in this country, and its effects are many and far-reaching. Many assume that a primary cause of political polarization is the increasing availability of ideologically tinged political news. Other scholars who have examined political polarization in news consumption have found that news audiences predominantly consume centrist or moderate news and for the most part ignored ideological news sources altogether. Yet the myth of ideologically driven news consumption doggedly persists. This paper finally dispels that myth by providing an examination of audience duplication among the fifty most popular political news sites in the month leading up to the November 2014 election. Using network analysis and web data provided by comScore, we argue that political news sites share more audiences than many realize, and that this holds true regardless of the political ideologies of either the audience or the outlet. We argue that a site’s popularity, rather than its ideology, is what drives political news consumption.